(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides some information about the fact that the serious study of the history of the Middle Stone Age of Central Asia began in the years of the former Soviet Union, and that the archaeologists of the Soviet era applied their ideas about the Middle Paleolithic settlements to the excavation processes.